Localization of vacuolar transport receptors and cargo proteins in the Golgi apparatus of developing Arabidopsis embryos - Hinz, Giselbert; Colanesi, Sarah; Hillmer, Stefan; Robinson, David G. (Traffic, 2007)
Using immunogold electron microscopy, we have investigated the relative distribution of two types of vacuolar sorting receptors (VSR) and two different types of lumenal cargo proteins, which are potential ligands for these receptors in the secretory pathway of developing Arabidopsis embryos. Interestingly, both cargo proteins are deposited in the protein storage vacuole, which is the only vacuole present during the bent-cotyledon stage of embryo development. Cruciferin and aleurain do not share the same pattern of distribution in the Golgi apparatus. Cruciferin is mainly detected in the cisand medial cisternae, especially at the rims where storage proteins aggregate into dense vesicles (DVs). Aleurain is found throughout the Golgi stack, particularly in the transcisternae and transGolgi network where clathrin-coated vesicles (CCVs) are formed. Nevertheless, aleurain was detected in both DV and CCV. VSR-At1, a VSR that recognizes N-terminal vacuolar sorting determinants (VSDs) of the NPIR type, localizes mainly to the transGolgi and is hardly detectable in DV. Receptor homology-transmembrane-RING H2 domain (RMR), a VSR that recognizes C-terminal VSDs, has a distribution that is very similar to that of cruciferin and is found in DV. Our results do not support a role for VSR-At1 in storage protein sorting, instead RMR proteins because of their distribution similar to that of cruciferin in the Golgi apparatus and their presence in DV are more likely candidates. Aleurain, which has an NPIR motif and seems to be primarily sorted via VSR-At1 into CCV, also possesses putative hydrophobic sorting determinants at its C-terminus that could allow the additional incorporation of this protein into DV.